The Conditional Relation between Beta and Returns in the Hong Kong Stock Market. - Ho, Wai Kit (2007)
In this dissertation some famous empirical studies of CAPM are reviewed. The validity of CAPM is further examined from the period of 2002 to 2006 for the HK Stock Exchange by utilizing the methodology suggested by Pettengill et al. (1995). I find that portfolio beta does play a significant role in explaining the cross-sectional returns under the condition that the market movement is taken into account. There is a positive significance beta-return relationship during the up market while there is a negative significance beta-return during the down market. This significance conditional result is contradictedwith the early empirical result studied by Black et al. (1972) and Fama and MacBeth (1973). Nevertheless, it should be noted CAPM have been seriously criticized by Roll (1977) whose argue that CAPM itself is non-testable.